2013
DOI: 10.3389/fimmu.2013.00381
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Supplementation with LGG Reduces Vaccine-Specific Immune Responses in Infants at High-Risk of Developing Allergic Disease

Abstract: Probiotics are defined as live micro-organisms that when administered in adequate amounts confer a health benefit on the host. Among their pleiotropic effects, inhibition of pathogen colonization at the mucosal surface as well as modulation of immune responses are widely recognized as the principal biological activities of probiotic bacteria. In recent times, the immune effects of probiotics have led to their application as vaccine adjuvants, offering a novel strategy for enhancing the efficacy of current vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…However, the mechanisms behind the proposed beneficial effects of probiotics in vaccination remain unknown. Although some of these studies report significant increases in vaccine-specific antibodies [57][58][59][60], the majority show modest or no effect of probiotics in providing major enhancement of antibody responses to vaccines [61][62][63][64][65]. Moreover, the outcomes of these studies are highly dependent on experimental conditions including strain and dose of probiotics, type of vaccine, and population studied.…”
Section: Impact Of Probiotics and Prebiotics On Vaccine Responsesmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the mechanisms behind the proposed beneficial effects of probiotics in vaccination remain unknown. Although some of these studies report significant increases in vaccine-specific antibodies [57][58][59][60], the majority show modest or no effect of probiotics in providing major enhancement of antibody responses to vaccines [61][62][63][64][65]. Moreover, the outcomes of these studies are highly dependent on experimental conditions including strain and dose of probiotics, type of vaccine, and population studied.…”
Section: Impact Of Probiotics and Prebiotics On Vaccine Responsesmentioning
confidence: 88%
“…Total IgG was similar in both groups [65] LGG (ATCC 52103) 5 Â 10 9 cfu, LGG (LC705) 5 Â 10 9 cfu, Bifidobacterium breve (Bbi99) 2 Â 10 8 cfu and Propionibacterium freudenreichii ssp. Shermanii JS 2 Â 10 9 cfu (n = 47).…”
Section: Impact Of Probiotics and Prebiotics On Vaccine Responsesmentioning
confidence: 91%
“…From a study within a larger clinical trial, the Lactobacillus rhamnosus GG (LGG) effect on immune responses to tetanus, Haemophilus influenza type b and pneumococcal conjugate vaccines in infants was assessed, in conjunction with the impact of maternal LGG supplementation in preventing the development of atopic eczema in infants at high-risk for developing allergic disease [ 52 ]. The study reported that maternal LGG supplementation was associated with reduced antibody responses against tetanus, Haemophilus influenza b, and pneumococcal conjugate compared to placebo treatment but not total IgG levels.…”
Section: Probiotics and Vaccinesmentioning
confidence: 99%
“…In contrast, a few studies have even reported a negative association between probiotics and vaccine responses. Maternal supplementation with Lactobacillus rhamnosus GG (LGG) was associated with a reduction in infant antibody responses to tetanus, Hib, and pneumococcus vaccines (88), and Bangladeshi children who received a 4-week course of BBG-01 had reduced levels of cholera toxin subunit B-specific IgA levels compared to controls (89). The administration of probiotics was associated with an increase in secretory IgA in stool samples of children at 5 months of age (90); however, this did not translate to improved clinical outcomes, as infants exposed to probiotics reported a higher frequency of mucosal infections up to 2 years of age, despite both groups being able to clear infections at comparable rates (90).…”
Section: Effects Of Probiotics On Vaccine Responsesmentioning
confidence: 99%